The significance of the Inao during the reign of King Chulalongkorn; A transitional period in the Thai Panji tradition - Jatuthasri, Thaneerat (UI Scholars Hub, 2020)
There are two main versions of the Panji story in the Thai literary tradition, entitled Inao and Dalang respectively. Both versions were first composed at the Thai court in roughly the eighteenth century and have provided inspiration for Thai arts ever since. Of the two stories, the Inao has become much more popular than the Dalang. The most influential Inao work was composed by King Rama II (r. 1809-1824) and his reign is widely accepted as the heyday of Inao. There was also another period of time in which the Inao theme was popular: the reign of King Chulalongkorn (r. 1868-1910). This article is an examination of the presentation of the Inao story during the reign of King Chulalongkorn and also presents an assessment of the significance of these Inao works to the Inao tradition. The findings of this article reveal that, during this period, the Inao story was presented in an increasingly diversified number of art and cultural works in both traditional and new styles. These Inao works marked a significant turning-point in the Inao culture and indicate that not only was the reign of King Chulalongkorn “a Golden Age” of the Inao in Thailand, but it was also “a transitional period” in the Thai Panji tradition.